Vincenzo Galilei and Music: Some Socio-Cultural and Acoustical Discussions - Bromberg, Carla; Alfonso-Goldfarb, Ana Maria (Circumscribere International Journal for the History of Science, 2009)
Vincenzo Galilei (1520?-1590) - father of Galileo Galilei- was a music theorist and lutenist. In his treatises he advocated that music was primarily based on physical phenomena, namely sound, and dismissed the Pythagorean-Platonic musical tradition based on number and ratio. Our aim in this article is to point out that Galilei viewed music as a physical phenomenum, sound, organized by natural as well as by socio-culturally defined rules.